The Social Space of Legal Life: A Theoretical and Conceptual Analysis of the "Rule of Law Cultural Square" - Li, Zefeng; You, Zongxiao (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
The Rule of Law Cultural Square, as a social space for legal life, represents a form of public space that embodies both Chinese characteristics and modern values. It integrates the orderliness of traditional Chinese squares with the openness characteristic of Western ones. Through architecture, sculpture, informational displays, and other mediums, it gives tangible and visible form to the ideals of the rule of law, enabling citizens to internalize legal norms and values subtly as part of their everyday lives. As a new frontier in legal education and public engagement, the Rule of Law Cultural Square embeds legal principles into the routines of ordinary people, serving as a spatial carrier for the formation and development of socialist rule of law practices with Chinese characteristics in the new era.